2016
DOI: 10.1002/tesj.280
|View full text |Cite
|
Sign up to set email alerts
|

Technology in Teaching English Language Learners: The Case of Three Middle School Teachers

Abstract: This study looks at how three middle school teachers of English as a second language (ESL) use technology in the classroom. Technology use in the ESL classroom has the potential of supporting the English and content learning of English language learners, but the availability of technology does not necessarily lead to technology integration that supports student learning. Teacher attitudes and beliefs toward technology as well as lack of time and adequate resources may deter teachers from integrating technology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 35 publications
(41 reference statements)
1
17
0
Order By: Relevance
“…According to Bullock (2004) teachers' attitude is the crucial factor that enables or disables them in their technology adoption. This was further supported by as study by Gonzalez & Harrell (2018) and Andrei (2017).…”
Section: Literature Reviewsupporting
confidence: 70%
“…According to Bullock (2004) teachers' attitude is the crucial factor that enables or disables them in their technology adoption. This was further supported by as study by Gonzalez & Harrell (2018) and Andrei (2017).…”
Section: Literature Reviewsupporting
confidence: 70%
“…Some studies have proven that technology involvement in students' learning drives to a new learning environment. A study showed that technology aided in empowering course learning relevancy with modern centered teaching (Andrei, 2017;Kim et al, 2013). In using the technology, teachers should focus on how it links and create a good interaction between the users and tools.…”
mentioning
confidence: 99%
“…The widespread use of laptops, smart phones and tablets means that traditional classroom based ESL is giving way to 'alternative, rapidly evolving' styles of teaching (Ghareb, Sate-Askew, & Mohammed, 2017). Whilst there is some recognition that increased availability of technology does not automatically mean better learning (Andrei, 2017), research still leans towards the positive effects of 1:1 devices. Criticality is perhaps lacking.…”
Section: The Positive Impacts Of Classroom Devicesmentioning
confidence: 99%